Isolation, Characterization and Virulence Potential of Tenacibaculum dicentrarchi in Salmonid Cultures in Chile. Issue 2 (8th January 2016) - Avendaño‐Herrera, R.; Irgang, R.; Sandoval, C.; Moreno‐Lira, P.; Houel, A.; Duchaud, E.; Poblete‐Morales, M.; Nicolas, P.; Ilardi, P.
Summary: In this study, we isolated, identified and characterized isolates of Tenacibaculum dicentrarchi in Atlantic salmon ( Salmo salar ) farmed in Chile for the first time. In 2010 and 2014, mortalities were observed in Atlantic salmon (average weight 25–30 and 480–520 g, respectively) at an aquaculture centre in Puerto Montt, Chile. Severe tail rots, frayed fins and, in some cases, damaged gills were detected. Wet smear analyses of these lesions revealed a high occurrence of Gram‐negative, filamentous bacteria. Microbiological analysis of infected gill and tail tissues yielded six bacterial isolates. All were identified as T. dicentrarchi through polyphasic taxonomy, which included phenotypic characterization, 16S rRNA sequencing and multilocus sequence typing. The latter method revealed a close relationship of the Chilean genotype with the T. dicentrarchi type strain and two Norwegian Atlantic cod ( Gadus morhua ) isolates. The pathogenic potential of the TdChD05 isolate was assessed by challenging Atlantic salmon and rainbow trout ( Oncorhynchus mykiss ) for one hour, which resulted in mean cumulative mortality rates of 65% and 93%, respectively, as well as clinical signs 14 days post‐challenge. However, challenged Coho salmon ( Oncorhynchus kisutch ) presented no mortalities or clinical signs of infection. These findings indicate that the geographical and host distribution of T. dicentrarchi is wider than previously established and that this bacterium may have negative impacts on salmonid cultures.